One-step synthesis of nitrogen-rich Mo2C1−xNx solid solution with enhanced superconductivity. Issue 8 (12th February 2020) - Zhang, Zhuang; Fang, Yuqiang; Wang, Dong; Zhang, Shaoning; Mu, Gang; Huang, Fuqiang
Abstract : It is difficult to prepare nitrogen-doped Mo2 C with high nitrogen content, and the effect of nitrogen doping on superconductivity of Mo2 C has not been studied. Abstract : A nitrogen doping strategy is often adopted to improve the superconductivity of Mo2 C for raising the Fermi surface, yet it is difficult to prepare Mo2 C with high nitrogen content. The highest doping content in the literature is only 1.36%, plus the preparation process is complex. In this work, a series of Mo2 C1− x N x solid solutions ( x ≤ 0.57) was prepared by simple solid-state reaction. The structure of Mo2 C is unchanged after nitrogen doping. The unit cell parameters changed with anisotropy. A change in superconductivity of Mo2 C has been observed. Its superconducting critical temperature ( T c ) is increased from 5.5 K to 7.9 K.